UPAYA PENINGKATAN KEMAMPUAN PENERAPAN TEKNOLOGI PENGOLAHAN PUPUK ORGANIK PADAT PADA PETERNAK SAPI POTONG DI DESA WORI KABUPATEN MINAHASA UTARA - Erwin Wantasen; Erwin H. B Sondakh; Umar Paputungan (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2018)
The aim of the activity was to know catttle farmers ability and their characteristics to implement technology of compact organic fertilizer made from cattle manure. The program was conducted in farmers group namely Lembah Pamuli located in Wori sub district regency of North Minahasa. The objects of activity consisted of 15 of cattle farmers whereas the materials included cattles manure, ureum, probiotic EM4 and other materials that can supported the processing of organic fertilizer production. The approach to the group was extension and training. The result of this program showed that 66.67% of the participant in extension and training was men and they were 43 years old in averages. Thirty percent of their level of education was elementary school, 40% in secondary school , 22% senior high school and 8% at level of diploma. According to pre and post test toward members group of Lembah Pamuli in line with their capacity to produce organic fertilizer showed that averages score increase by 47.94% after they followed the extension and training to produce organic fertilizer.